EDUKASI BUNDA TENTANG TUMBUH KEMBANG BALITA DENGAN BUKU SAKU “TEMAN BUNDA” - Nikmah, Nurun; Qomari, Selvia Nurul; Antina, Rila Rindi (JURNAL PARADIGMA (PEMBERDAYAAN & PENGABDIAN KEPADA MASYARAKAT), 2025)
Mothers play a pivotal role in supporting the optimal growth and development of toddlers, making maternal knowledge an essential factor in this process. Adequate understanding enables mothers to implement appropriate developmental support strategies. This community service program aimed to enhance maternal knowledge regarding toddler growth and development through the use of the Teman Bunda pocket book. The activity was conducted by administering a pre-test questionnaire, followed by the provision of educational materials utilizing the printed pocket book. Findings demonstrated a significant improvement in maternal knowledge, with the proportion of knowledgeable mothers increasing from 42 (48%) prior to the intervention to 56 (64%) after the intervention. These results indicate that structured education combined with the Teman Bunda pocket book is effective in improving maternal knowledge of toddler growth and development.